Effect of irrigation regimes and nutrient levels on growth, yield and quality of drip irrigated broad bean (Vicia faba) - GUPTA, SANGEETA; KUSHWAH, S S; SHARMA, R K; SINGH, O P (The Indian Journal of Agricultural Sciences, 2017)
A field experiment was conducted to study the effect of irrigation regimes and nutrient levels on growth, yield, quality, economics and water use efficiency (WUE) of broad bean at College of Horticulture, Mandsaur during rabi 2015-16. Treatments included three irrigation regimes, viz. I1 (IW/CPE=1.00), I2 (IW/CPE=0.75), I3 (IW/CPE=0.50) and three nutrient levels, viz. F1 (15:40:30 kg NPK/ha), F2 (30:60:45 kg NPK/ha) and F3 (45:80:60 kg NPK/ha). These treatments were evaluated under split plot design with 6 replications. Results indicated that irrigation level I1 (IW/CPE=1.00) recorded maximum plant height, number of tillers/plant, number of leaves/plant, leaf area/plant, most delayed 50% flowering and pod maturity, maximum length of pod, number of pod/plant, number of seeds/pod, weight of 10 pods, pod yield/plant, pod yield/hr and fibre content in pod. It was followed by I2 (IW/CPE=0.75). Highest protein content was found under I3 (IW/CPE=0.50). WUE decreased with higher irrigation regimes and was observed lowest with I1 (IW/CPE=1.00). Among nutrient levels, F3 (45:80:60 kg NPK/ha) registered maximum growth, phenological, yield attributes and yield as well as protein and fibre content. It has also recorded highest WUE. Interactive effect of irrigation regimes and nutrient levels showed highest growth and yield attributes as well as yield with I1F3. Highest WUE was recorded with I3F2 which was at par to I3F3. Maximum gross return (Rupees 154 770/ha), net return (Rupees 113 820/ha) and benefit:cost ratio (2.77) was obtained with application of I1F3.